The foreign language classroom anxiety scale in the South African context: Drumming to a different beat? - Grobler, Carina; Fourie, Erika (Journal for Language Teaching, 2025)
Anxiety in language learning has been studied for decades. One of the most widely used instruments allowing researchers to investigate this phenomenon is the Foreign Language Classroom Anxiety Scale (FLCAS). Only a limited number of studies have investigated the psychometric properties of the questionnaire to gauge the validity (factor analyses) and reliability (Cronbach Alphas) of the indicated factors and items for their specific context. The present study adopted a wider approach by including Rasch analyses to adjust the FLCAS for use in the South African context. Before submitting the questionnaire to 124 first-year students in French a translated version was prepared to ensure cultural adaptability. The investigation was iterative and was conducted in two cycles which included exploratory and confirmatory factor analyses, Cronbach’s Alpha and Rasch analyses to arrive at a proposed model to ensure sound measurement of foreign language anxiety for the specific context. Results point to three factors with 25 relevant items. The original FLCAS was thus improved for the specific context by eliminating problematic items highlighted by the analyses and regrouping the remaining items into the three uniquely South African factors. This represents a first analysis from a Rasch analysis perspective in this context.